Circulation of water and sediment in the Athabasca Delta area ... - Lipsett, A. W.; Neill, C. R.; Evans, B. J. (University of Alberta Library, 1981)
The objective of the study was to describe how water and sediment from the Athabasca River are distributed through the delta system and how they circulate and mix in Lake Athabasca and flow through to the Slave River, with a view to understanding the pathways ano destinations of contaminants that might reach the Athabasca River. Study components included literature reviews, remote sensing interpretations, field investigations and mathematical analyses. The project was viewed as a first stage study to sketch the essentials of the system and to outline needs and methodologies for a better definition. ...